Epidemiological Record of Permanent Artificial Cardiac Pacemaker Implant at a Reference Center - Goldoni, Larissa Freitas Nunes; Sales, Rafaela Louise; Luciano, Kárila Scarduelli; Kraus, Alessandra; Ronsoni, Rafael de March (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Objective: To identify the profile of patients who implanted pacemakers and their complications in a tertiary cardiology center in the state of Santa Catarina. Methods: Unicentric, observational and prospective study with 81 patients submitted to pacemaker implantation by the Cardiovascular Surgery Service. Results: Provisional pacemaker was necessary in 42 cases (51.8%) and the average time of temporary pacemaker insertion was 2.2 days. Death occurred in 3 patients (3.7%), however only 1 case (1.2%) was associated with the implant. Conclusion: The clinical characteristics and indications of the implant in the study population were similar to those found in the literature, however the number of complications was high and the length of stay of the provisional pacemaker is beyond that recommended.